Amyloidosis and Heart Failure with preserved ejection fraction, a more commom association than current epidemiological descriptions: Case Report - Oliveira Potratz, Mateus (2021)
Amyloidosis is a disease characterized by the deposition of amyloid fibrils. When deposited in the heart, they can cause conduction disturbance, restrictive cardiomyopathy, diastolic dysfunction, low output and preserved ejection fraction heart failure (HFpEF), mainly related to transthyretin (TTR). Case description: A 70-year-old man, hypertensive, diabetic and dyslipidemic sought a cardiologist complaining of dyspnea on mild exertion, hyporexia, adynamia and edema in the lower limbs, with jugular turgescence at 45º and second heart sound hyperphonesis on cardiac auscultation. Complementary workup started to better elucidate the etiology of heart failure with electrocardiogram at rest showing low voltage, type B natriuretic peptide in the value of 3920 pg/ml, echocardiogram with biatrial enlargement, concentric hypertrophy of the left ventricle, global systolic function of the left ventricle preserved with an ejection fraction of 65%, hypertrophic septum and a heterogeneous and hyperrefringent infiltrative appearance. Due to the suspicion of amyloidosis, an investigation was carried out with cardiac magnetic resonance, which demonstrated late subendocardial enhancement characteristic of the pathology, and later a genetic test for amyloidosis of familial origin associated with variants in the TTR gene, confirming the diagnosis. Conclusion: Cardiac amyloidosis is a condition described as rare, but with numerous underdiagnosed cases. Conditions previously attributed to normal aging are likely due to cardiac amyloid deposits, leading to HFpEF. The existence of less invasive diagnostic methods, especially with dissociation between echocardiogram and electrocardiogram, contribute to early diagnosis, treatment plan and improved prognosis, modifying the natural history of the disease, avoiding the deposition of fibrils in the tissues.